1992
DOI: 10.7326/0003-4819-117-10-831
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Left Ventricular Hypertrophy in Patients with or without Coronary Artery Disease

Abstract: Echocardiographically determined left ventricular hypertrophy is an important prognostic marker in patients with or without coronary artery disease. The effect of reversing ventricular hypertrophy in patients with and without coronary disease deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
201
1
8

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(218 citation statements)
references
References 29 publications
7
201
1
8
Order By: Relevance
“…In a study carried out in a predominantly black population with established CAD, the prevalence of echocardiography (echo) LVH was as high as 50%. 2 We recently found similar figures, 3 while according to Framingham, the prevalence would be around 30-35% in controls. Secondly, in a comparative study in CAD patients, Liao et al 4 showed that the independent relative risk of cardiac death conferred by LVH was higher (2.4) and accounted for more deaths than multivessel coronary disease (relative risk ¼ 1.6) or LV systolic dysfunction (relative risk ¼ 2.0).…”
Section: Introductionmentioning
confidence: 63%
“…In a study carried out in a predominantly black population with established CAD, the prevalence of echocardiography (echo) LVH was as high as 50%. 2 We recently found similar figures, 3 while according to Framingham, the prevalence would be around 30-35% in controls. Secondly, in a comparative study in CAD patients, Liao et al 4 showed that the independent relative risk of cardiac death conferred by LVH was higher (2.4) and accounted for more deaths than multivessel coronary disease (relative risk ¼ 1.6) or LV systolic dysfunction (relative risk ¼ 2.0).…”
Section: Introductionmentioning
confidence: 63%
“…Emerging data from echocardiographic investigations indicate that increased left ventricular mass is associated with greater risk for cardiovascular morbidity and mortality. [19][20][21][22] Echocardiographic studies also reveal that antihypertensive treatment can regress LVH in selected hypertensive patients.2324 However, it is not known if regression of LVH on the echocardiogram or on the ECG will reduce the excess burden of cardiovascular disease associated with this condition.…”
mentioning
confidence: 99%
“…1,2 The prognostic relevance of LV geometry has also been investigated. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Various studies [3][4][5][6] have repeatedly reported that LV hypertrophy is associated with increased cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%